1968
DOI: 10.1063/1.1668895
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Isolation Study of the Hydrogen Cyanide Dimer

Abstract: On the basis of the infrared spectra of HCN and DCN in Ar, N2, and CO matrices at temperatures from 4.5° to 20.5°K, it is concluded that there is no evidence for rotation of the monomeric species in these matrices and that the dimer has a linear or nearly linear HCN·HCN structure. The Lippincott-type potential is used to calculate frequencies for the stretching of the hydrogen bond and for the torsion about the hydrogen bond. These calculated frequencies are compared with our observed far-infrared spectra of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

1969
1969
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 20 publications
7
35
1
Order By: Relevance
“…Accurate vapour phase data are available for v2 [22,26], the hydrogen bonded C-H stretch, v a and v 4 [26], the C~N vibrations, v s [18], the intermolecular stretch and v9 [21], the lowest lying intermolecular bending vibration. Low temperature matrix isolation studies have scanned intramolecular stretching [28-31, 33, 34] and bending regions [28][29][30][31]. Far infrared investigations in different matrices on low lying intermolecular modes are also available [28,[32][33][34].…”
Section: Vibrational Frequencies and Infrared Intensitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate vapour phase data are available for v2 [22,26], the hydrogen bonded C-H stretch, v a and v 4 [26], the C~N vibrations, v s [18], the intermolecular stretch and v9 [21], the lowest lying intermolecular bending vibration. Low temperature matrix isolation studies have scanned intramolecular stretching [28-31, 33, 34] and bending regions [28][29][30][31]. Far infrared investigations in different matrices on low lying intermolecular modes are also available [28,[32][33][34].…”
Section: Vibrational Frequencies and Infrared Intensitiesmentioning
confidence: 99%
“…Low temperature matrix isolation studies have scanned intramolecular stretching [28-31, 33, 34] and bending regions [28][29][30][31]. Far infrared investigations in different matrices on low lying intermolecular modes are also available [28,[32][33][34]. The qualitative picture emerging both from SCF [42,43] and our CPF calculations agrees well with the experimentally observed trends in the vapour phase and by matrix spectroscopy as far as intramolecular modes are concerned (o91-o96)-The CPF results for o9s and o99 are also in close agreement with the gas phase data.…”
Section: Vibrational Frequencies and Infrared Intensitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An infrared study of HCN and DCN isolated in various solid matrices has also been published (10). Our main purpose in undertaking the present study was to determine solid phases were consistent with the reported crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers reported the bands of HC^N in the gas phase 30 and in the low-temperature matrices 23,[31][32][33][34] to be $3303 and $720 cm À1 for the C-H stretching and bending modes, respectively. The 3304 cm À1 and 715 cm À1 bands observed in Fig.…”
Section: Photodecompositions By Two Cleavages Of the S1-c2 And N3-c4 mentioning
confidence: 99%